Determinan Green Human Resouce Management terhadap Komitmen Karyawan dengan Motivasi Kerja Sebagai Variabel Moderasi pada Dinas Perhubungan Sumatera Barat - Charli, Chintya Ones; Mahzum, Muhammad (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
This study aims to analyze the effect of Green Human Resource Management (GHRM) on employee commitment, with work motivation as a moderating variable at the West Sumatra Department of Transportation. This research employs a quantitative method with an explanatory research approach, collecting data through a survey of 95 employees and analyzing it using SEM-PLS. The results indicate that GHRM has a positive and significant effect on employee commitment. Work motivation also significantly influences commitment but fails to moderate the relationship between GHRM and employee commitment. These findings confirm that effective GHRM implementation can enhance employee loyalty and engagement without being influenced by individual motivation levels. This study provides implications for organizations in developing environmentally-oriented human resource policies to improve employee performance and retention.